Screening of groundnut genotypes for phosphorus efficiency under field conditions - Singh, A.L.; Chaudhari, Vidya; Ajay, B.C. (The Indian Journal of Genetics and Plant Breeding, 2016)
Groundnut is an important legume of tropical world where phosphorus (P) deficiency is one of the limiting factors affecting productivity and use of P-efficient genotype is the solution. Thus P-efficiency among seventy groundnut genotypes was studied under P-deficit (-P) and adequateP (+P) condition by recording yield and its attributes and calculating various P-efficiency indices. Significant differences among groundnut genotypes, P levels and their interactions were observed for all the traits and the range of pod yield was 3.4-10.5 g plant-1 under -P and 4.1-12.8 g plant-1 at +P, 100 seed mass was 23-68 g. The range of phosphorus stress factor (PSF) was -40 to 39 in pod (PSFp) and -142 to 45 in haulm (PSFh), P efficiency (PE) was 0.61-1.40 in pod (PEp) and 0.55-2.42 in haulm (PEh) and agronomic P use efficiency was 14 to 29. Genotypes were divided into efficient, inefficient and moderate based on the P-efficiency index (PEI), but into efficient and inefficient, responder and non-responder, using PEI and pod yielding potential. The efficient responders genotypes GG 5, PBS 11037, PBS 11046, PBS 13007, PBS 20505 and SP 250A with low PSF, high PEI and, PE close to unity were identified for P-deficit soils.